The fine evaluation and optimization strategy of barrier-free public activity systems from the perspective of a county-level city: Xinle, Hebei Province - Zhang, Sen; Zhang, Ke; Zhao, Haoge; Zhang, Jiahao; Chen, Jianyu (Frontiers in Built Environment, 2025)
IntroductionCompared with prefecture-level cities and other large cities, county-level cities in China have significant differences in composition of public service facilities, population size characteristics, and social awareness. Thus, it is necessary to conduct refined research on barrier-free design and evaluation in county-level cities.MethodsWe used Xinle as an example based on the composition of vulnerable groups and people’s spatio-temporal activity data from the perspectives of public service facilities, tactile paving systems, and activity areas to explore the construction approach and current situation of barrier-free public activity systems (PAS).ResultThe main vulnerable groups in Xinle those who are the elderly, visually impaired, and mobility-impaired individuals. Among these groups, common needs characteristics can be found in the area of shopping consumption and company and enterprise, non-common characteristics centered around food and beverages, life services, healthcare, and parking lots. Then the spatial distribution of related public service facilities is vital for building barrier-free environments. At the same time, the tactile paving system in Xinle has weak correlation with key facilities and poor construction standards.DiscussionFrom this, optimization strategies for a barrier-free PAS is construct in this research and to provide theoretical and technical references for county-level cities to carry out related work.